Atenção psicossocial : entre o transtorno mental e o território - Ribeiro, Wallace de Lima (2009)
This paper examines the process of deinstitutionalization of madness in the network of relationships between practices, discourses and knowledge, involving the Center for Psychosocial Care (CAPS) in the municipality of Guarapari - ES. Was used as a methodological resource mapping to monitor the lines and trends of Psychiatric Reform process. Thus, the research involves an ethical-political stance in favor of life, which involves processes that may emerge in the new sensitivities, new expressions, new ways of thinking and acting, short of new possibilities to face life. Was used to search different sources. Operators now emerged of conceptual references, some documents, either from contact with people who attend the CAPS, now the observation of activities, some interviews scheduled, either in informal conversations, sometimes for walks, to make visible the practices of psychosocial care taken in CAPS. You can follow, therefore, that the practices, discourses and knowledge about the psychosocial care is an agency set of lines of forces. On one hand the practices, discourses and knowledge, encoded with a line-clinical biomedical sciences, with the diagnosis / prognosis / treatment, which produces severe and persistent mental disorder. In addition, a line of appliances to coding in the state. Among them, is a line of action written in the territory, it takes practice and discourse outside the walls of the asylum, which involves a role in society, a struggle for cultural change, in respect for differences, for rights and citizenship for patient psychiatric, finally, is a line drawn in the movement in the city.